2018
DOI: 10.1080/13575279.2018.1448257
|View full text |Cite
|
Sign up to set email alerts
|

It’s Not a Case of He’ll Be Home One Day.” The Impact on Families of Sentences of Imprisonment for Public Protection (IPP)

Abstract: There is now a growing body of literature which is centred upon the negative outcomes that occur for many families, and by extension, children who experience the imprisonment of a father. Typically families suffer the consequences of living with stigma and financial difficulties, while children are often affected by being provided with limited information about what has happened to their incarcerated parent. These factors can combine to increase the chances of children and family members in this position devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Although, these adverse experiences have been found to be ‘generic’ for relatives of offenders, the indeterminacy of the IPP sentence tends to exacerbate these. The prevalence of mental health issues experienced by the family members of IPP‐prisoners has been identified by McConnell and Raikes (2019), for example, as a common theme arising in their research. Comparing mental and emotional effects on family members of indeterminate versus determinate sentenced prisoners, the Children of Prisoners Interventions and Mitigations to Strengthen Mental Health (COPING) pan‐European study (Jones et al, 2013) concluded that these were experiencing different stress levels.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Although, these adverse experiences have been found to be ‘generic’ for relatives of offenders, the indeterminacy of the IPP sentence tends to exacerbate these. The prevalence of mental health issues experienced by the family members of IPP‐prisoners has been identified by McConnell and Raikes (2019), for example, as a common theme arising in their research. Comparing mental and emotional effects on family members of indeterminate versus determinate sentenced prisoners, the Children of Prisoners Interventions and Mitigations to Strengthen Mental Health (COPING) pan‐European study (Jones et al, 2013) concluded that these were experiencing different stress levels.…”
Section: Resultsmentioning
confidence: 97%
“…Distinct relief was experienced by prisoners and families when a determinate sentence was awarded, since it provided a release date to work toward (Jones et al, 2013). As McConnell and Raikes (2019, p. 4) have noted:
this is not the case for those subject to IPPs and other indeterminate sentences and their families. They continue to experience the anxiety associated with uncertainty long after they are sentenced.
…”
Section: Resultsmentioning
confidence: 99%
“…Almost half of these had been recalled to custody after release. These offenders often present a continued risk of offending, and are more likely than the average prisoner to experience mental illness and substance addiction (McConnell & Raikes, 2019; Rutherford, 2009), but there is pressure on the Parole Board to move such prisoners out of a penal system which may exacerbate those problems (Annison & Condry, 2022; Straub & Annison, 2020).…”
Section: Parole Board Decisionsmentioning
confidence: 99%
“…Parental incarceration is taken as a household dysfunction, closely connected to poor health behaviors like smoking, alcohol dependency and obesity, and poorer socio-economic achievement (lower education and income) in adulthood (Westermair et al, 2018). A recent study (McConnell and Raikes, 2019) showed that the negative impact on children is even worse in the case of an Imprisonment for Public Protection (IPP) scheme where there is no definite release date.…”
Section: Introductionmentioning
confidence: 99%